Dynamic changes of B‐cell compartments in kidney transplantation: lack of transitional B cells is associated with allograft rejection. (24th February 2016) - Svachova, Veronika; Sekerkova, Alena; Hruba, Petra; Tycova, Irena; Rodova, Marketa; Cecrdlova, Eva; Slatinska, Janka; Honsova, Eva; Striz, Ilja; Viklicky, Ondrej
Summary: B cells play an important role in the immune responses which affect the outcomes of kidney allografts. Dynamic changes of B‐cell compartments in clinical kidney transplantation are still poorly understood. B‐cell subsets were prospectively monitored using flow cytometry for 1 year in 98 kidney transplant recipients. Data were correlated with immunosuppression and clinical outcomes. An increase in the total population of B lymphocytes was observed during the first week after transplantation. The level of IgM high CD38 high CD24 high transitional B cells reduced significantly up until the third month, with partial repopulation in the first year. Lower numbers of transitional B cells in the third month were associated with higher risk of graft rejection. IgM + IgD + CD27 − naive B cells did not change within follow‐up. IgM + CD27 + nonswitched memory B cells and IgM − CD27 + switched memory B cells increased on post‐operative day 7. IgM − CD38 high CD27 high plasmablasts showed similar kinetics during the first post‐transplant year, similar to transitional B cells. In conclusion, sensitized kidney transplant recipients as well as those with either acute or chronic rejection within the first post‐transplant year exhibited lower levels of transitional B cells. Therefore, these data further support the hypothesis that transitional B cells have a protective role in kidney transplantation.